Peace process in Mindanao, the Philippines from 1972 to 1976 - คำโพธิ์ทอง, รวินทร์ (Journal of Politics and Governance, 2018)
This article aims to study conflicts solving in Mindanao between separatist groups and Ferdinand Marcos's government in 1972-1976 because violence became more and more severe and intense. The main causes were from the economy policy and the policy of ethnicity and the difference of religious back ground between Moro people who are Muslims whereas the rest are Catholics. The study showed that conflicts and the attempt to separate became very obvious. Students and educated people network was formed . Conflicts with Muslims and political problems led to the higher level of violence during Marcos's governing. Certain problems were; 1) Jabidah Massacre in 1968 of Moro people in Sabah island. This led to the forming of important Muslim groups which are Muslim Independence Movement (MIM) in 1968 and Moro National Liberation Front (MNLF) in 1969. 2) Conflicts and war between Moro people and the Christians in Cotabato, Mindanao in 1970. 3) Protests of students, labors and Muslim groups toward Marcos's government in 1970-1972. With all those protests, Ferdinand Marcos decided to declare the martial law in September 21, 1972. After this law was declared, tensions and conflicts became more severe in the southern part of the country. However, conflicts and violence solving during Ferdinand Marcos's government in 1972-1976 was not succeeded because they didn't put enough effort and sincerity, especially the failed of Tripoli Agreement. But, this failure was the important lesson to build peace for the next government of Corazón Aquino, the 11th president, and later Fidel Ramos, the 12th president. This study describes the causes the attempt to separate, the details of peace process in the Philippines which was Tripoli Agreement in 1972, and the results during Ferdinand Marcos's times.